A Hermeneutic comparative study on Amina Wadud's and Mohammed Talbi's interpretation of Q. 4:34 - Afifur Rochman Sya'rani (Departement of Qur'anic Studies Faculty of Ushuluddin and Islamic Thought Sunan Kalijaga State Islamic University, 2016)
st,1/ws.c.1